PENGEMBANGAN SEKOLAH BERBASIS ASET UNTUK MEWUJUDKAN MERDEKA BELAJAR - Kurniawan, Gede Benny (Prosiding Temu Ilmiah Nasional Guru, 2023)
This best practice was conducted with the purpose of resolving the issues faced by SMAN 2 Tejakula. The school had issues in various aspects, to the point where it could only manage to earn B category rating for its accreditation. These include the attempts to explore the potentials that the school and its surrounding community possess. One of the agreed solutions is the asset-based school development approach. Entrepreneurship classes offered to the students are tailored to their interests and talents. Nine entrepreneurship classes have been established, namely: Wajah Plastik class, Smandala Marine Class, Coffee Class, Dodol (Sweet Toffee) Class, Incense Class, Bouqet Class, Make up Class, Broadcasting Class, and Upcycle Class. This planned program has been running well thanks to the collaboration among the resources possessed by the school community, which include teachers, non-teaching staff, students, the surrounding local community, parents, school committee, village government, entrepreneurs, universities, alumni, and others. In addition, this success was determined by the convenience of students in learning. Students learn based on their interests, and the learning that takes place utilizes the school's potentials. Thus, this implementation of Asset-Based School Development was able to realize the idea of independent learning (Merdeka Belajar).